The Role of Total Quality Management Strategies in Resource Sustainability in Strategic Projects: An Analytical Study of the Opinions of a Sample of Employees at the Kufa Cement Plant: Peran Strategi Manajemen Mutu Total dalam Keberlanjutan Sumber Daya pada Proyek-Proyek Strategis: Studi Analitis terhadap Pendapat Sebagian Karyawan di Pabrik Semen Kufa - Hashim, Muntaha Manate (Indonesian Journal of Public Policy Review, 2026)
General Background: Total Quality Management (TQM) has evolved into a strategic approach for improving organizational processes and long-term sustainability in competitive environments. Specific Background: In industrial settings, integrating TQM strategies into strategic projects is increasingly associated with efficient resource utilization and sustainability outcomes. Knowledge Gap: However, limited empirical evidence exists on how specific TQM dimensions contribute to resource sustainability within strategic project contexts, particularly in developing economies. Aims: This study examines the relationship between TQM strategies and resource sustainability in strategic projects at the Kufa Cement Plant. Results: Using data from 135 employees and structural equation modeling, the findings reveal a significant positive relationship between TQM strategies and resource sustainability, with leadership, supplier development, and continuous improvement showing strong contributions. Novelty: The study introduces an integrated model linking TQM dimensions with sustainability outcomes in an industrial project setting. Implications: The results provide practical insights for organizations seeking to reduce waste, optimize resources, and support long-term sustainability through strategic quality management practices. Keywords: Total Quality Management, Resource Sustainability, Strategic Projects, Continuous Improvement, Industrial Management Key Findings Highlights Leadership-driven quality practices show the strongest contribution to sustainable resource utilization Supplier collaboration supports long-term operational stability and material efficiency Continuous process refinement reduces waste and sustains production cycles